The Role of Services for Economic Performance in Brazil - Arbache, Jorge (OECD Publishing, 2016)
This paper highlights the large contribution of services to the Brazilian economy and the under-exploited potential of services to sustain productivity gains and international competitiveness. The areas with the largest potential for regulatory reform include improvements in the general business and trading environment as well as specific policies in transport sectors, telecoms and financial services. Reforms targeting services that add value by favouring productivity and quality enhancements, as well as services that increase efficiency by reducing production costs, have strong potential to unlock manufacturing performance. The set of proposed recommendations emerging from this analysis underlines the importance of streamlining sector-level regulatory frameworks to encourage foreign entry and competition, and the role that cross-cutting improvements in the trade and business environment would play to render services providers more competitive
Keywords: Trade; Brazil